Aplicações de fungicidas em estádios fenológicos do milho para controle de podridão da base do colmo e seus efeitos em variáveis agronômicas - Fiametti , Mayara Suê (2022)
In recent years, maize has assumed great importance in the national economy, leading producers to adopt some management practices, such as successive crops, which result in an increase in phytosanitary problems, such as stem diseases. The objective of this work was to verify the effectiveness of the application of two fungicides to control stem base rot and its effects on agronomic variables. The experiment was conducted in Toledo - PR, during the second harvest (safrinha) of 2021. The experimental design used was in randomized blocks in a 5 x 2 factorial scheme, with five replications. The first factor refers to the phenological stages of fungicide application (V4, V8, V4+V8 and V4+V8+V12, in addition to untreated control) and the second factor refers to the fungicides (trifloxystrobin + prothioconazole and pyraclostrobin + fluxapyroxad). Plant height, ear insertion height, stem diameter, number of rows per cob, number of grains per row, thousand-grain mass, yield and incidence of stem base rot were evaluated. Based on the phenological stages of fungicide application, there was only statistical difference for plant height and stem base rot incidence. In the V4 stage, the observed plant height exceeded the control and the V4+V8 stage, with differences of 4.8 and 4.0%, respectively. Regarding fungicides, it was only verified in plant height and productivity. With the use of pyraclostrobin + fluxapyroxad, the production was 7% higher than when trifloxystrobin + prothioconazole were used. The fungicides were more effective to control corn stalk base rot when applied in the V4 + V8 + V12 vegetative stages. The agronomic variables, number of rows per cob, number of grains per row and mass of one thousand grains were not influenced by the application of fungicides. The application of the fungicides pyraclostrobin + fluxapyroxad provided higher productivity.